Family Reintegration: A Healing Process of Traumatic Effect in Sam Shepherd’s Buried Child - Poudel, Dinesh Kumar (Adhyayan Journal, 2025)
This article explores the dimension of family trauma and healing in Sam Shepherd’s play Buried Child through a Freudian lens. It investigates how repressed secrets of the Dodge family, the murder of an infant born out of incest relation between the mother of the family, Halie, and her eldest son Tilden affect the psychological and emotional well-being, economic affairs and interpersonal relation. It investigates how repressed secrets within the Dodge family, particularly the hidden crime of filicide, affect their psychological and emotional wellbeing. Based on Freudian theories of repression and catharsis, this article examines how the eventual confession of the crime leads to the process of healing and family reintegration. Analyzing the repressed psychic pain and their healing through confession, the article argues repression of painful secrets would disintegrate the family ties which can be healed through confession and leads to psychological relief and reintegration.